Reflectance confocal microscopy in the treatment monitoring of androgenetic alopecia topical combination therapy: Reflectance Confocal Microscopy for Treatment Monitoring of Androgenetic Alopecia - Rubin, Alexandra; Jamgochian, Marielle; Razi, Shazli; Truong, Thu; Al-Tariq, Kabir; Rao, Babar (Journal of Pakistan Association of Dermatologists, 2023)
Androgenetic alopecia (AGA) is the most common type of non-scarring alopecia. While global photography is the most commonly employed to track therapeutic efficacy, reflectance confocal microscopy (RCM) is a non-invasive imaging tool that may offer novel insights in tracking treatment progression for AGA. Ten patients with androgenetic alopecia initiating topical combination therapy elected to undergo treatment monitoring of this formulation using global photography and/or reflectance confocal microscopy. All patients had evidence of follicular miniaturization at baseline, and rimmed dermal papillae at both baseline and the end of the study. One patient had follicular miniaturization at baseline but not at the end of the study; however, this patient did not exhibit any changes in their Hamilton Norwood Score. Two patients exhibited inflammatory cells in the epidermis of the frontal scalp and mid-scalp at baseline on RCM that were no longer visible on RCM after 12 weeks of treatment. Of these two patients, one patient had a Hamilton Norwood score that did not improve after treatment, even though inflammatory cells were no longer present post-treatment. RCM offers a novel, non-invasive option for monitoring sub-clinical treatment progress in patients with AGA that can uncover novel insights in patients’ presentation and response to treatment earlier than with global photography.